Monitoring the Estrogenic Activities of the Metabolites of Bisphenol A, F and S During Sphingobium Fuliginis OMI-Mediated Biodegradation - Dang, Minh Hieu; Tokura, Koichiro; Kuroda, Masashi; Ike, Michihiko (Old Journal, 2017)
Bisphenol A (BPA) and its isomers: bisphenol S (BPS) and biphenol F (BPF) have been found in vast number of applications from join and coating materials to everyday items. The release of these chemicals into environments has received great concerns recently and has been reported to associate with various toxicities in animals and human. Among those toxicities, estrogenicity is in high attention since not only BPA and its isomers but also various compounds created during their metabolism can mimic the activity of estrogen in endocrine system. In this study, the estrogenic activities of the metablites created during the biodgradation of BPA, BPF and BPS were monitored. The strain Sphingobium fuliginis OMI was found efficient to remove the bisphenols from mediums. However, study also revealed that the estrogenic activity, in general, remained during the whole biodegradation experiment. It even showed a little increase in the case of BPS at 20 hours after starting the degradation.